Songspirals Bring Country Into Existence: Singing More-Than-Human and Relational Creativity. (June 2022) - Country, Bawaka; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr-Stubbs, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil; Lloyd, Kate; Wright, Sarah; Suchet-Pearson, Sandie; Daley, Lara
Songspirals bring Country into existence. Co-authored by a more-than-human, Yolŋu-led collaboration, this article centers Yolŋu understandings of time and place and elaborates on our work together through a spiral-based framework. Our Indigenous and Country-led Collective nourishes and shares some Yolŋu understandings of songspirals to enable, enrich, and awaken Country; to challenge and expand Western academic frameworks; and to contribute toward more responsive relationships between people and places. To sing or keen the spirals now means the ongoing creation of place and people—an emergent, more-than-human creativity that literally creates and re-creates existence. Songspirals are more-than-human processes that need active engagement to nourish positive relationships and to heal damaged ones. Songspirals are a keening/singing, of, with, by, for, and as Country.